ISLAMIC BANK FINANCING ACCESS AND FINANCIAL LITERACY ON MSME GROWTH: DIGITAL LITERACY AS MODERATOR - Abdillah Nurul Bahri; Muhammad Ridha Irsyadillah; Khoirul Anwar (Journal of Management and Islamic Finance, 2025)
This study aims to analyze the influence of access to Islamic bank financing and Islamic financial literacy on the growth of MSMEs in Semarang City, as well as examine the role of digital literacy as a moderation variable. The background of this research is based on the low level of utilization of sharia financing and financial literacy by MSMEs actors, as well as the importance of digital literacy in supporting business success in the digital era. This study uses a quantitative approach with primary data collected through an online questionnaire and analyzed using the Partial Least Square (PLS) method through the SmartPLS application. The research sample consisted of 102 MSMEs actors selected based on the Slovin formula. The results of the study show that access to Islamic bank financing and Islamic financial literacy have a positive and significant influence on the growth of MSMEs. However, digital literacy does not have a direct effect on the growth of MSMEs and is also unable to moderate the relationship between access to financing and financial literacy to the growth of MSMEs significantly. This shows that digital literacy has not played an optimal role as a reinforcing variable in this context. This research provides important implications for Islamic financial institutions, local governments, and MSMEs actors in designing financial and digital capacity building strategies to encourage more sustainable and competitive business growth.